The role of psychooncology in cancer treatment - a literature review - Karolina Jaglarz; Maciej Kuca; Marcin Cholewa; Julia Wójcik; Kacper Wojciech Pamuła; Wiktoria Maria Szymańska; Julia Plewniok; Maria Partyka; Maksymilian Janeczek; Karolina Kinga Kantor (Kazimierz Wielki University, 2024)
Introduction and objective. Receiving a cancer diagnosis can lead to significant mental distress, highlighting the necessity for comprehensive medical care that includes psychological support. Effective psycho-oncological therapy can help patients find fulfillment regardless of their prognosis, while also improving overall outcomes and treatment adherence. This article aims to review the medical literature on the mental health challenges faced by cancer patients and to explore potential treatment modalities. Review methods. Implementing Google Scholar and PubMed, a literature analysis was conducted, with particular attention paid to terms like "psychooncology," "anxiety," "depression," "cancer," "grief," and "PTSD." The period of consideration for articles was from 2017 to 2024. Brief description of the state of knowledge. Grief, anxiety, PTSD, despair, and other mental health problems can arise after receiving a cancer diagnosis. In order to improve treatment adherence and survival rates, psychological well-being must be addressed. Empirical evidence indicates that psychological disorders can hinder adherence to therapy and elevate the risk of death from cancer. Furthermore, as families often endure significant stress throughout the disease, psychological care is beneficial to both patients and their relatives. It is possible to enhance adherence and reduce symptoms by using an integrated strategy that takes into consideration both physical and mental health. Conclusions. An essential part of holistic cancer care is psycho-oncology, which enhances patients' general health and quality of life. Psycho-oncological therapy must be incorporated into standard cancer care in order to improve treatment outcomes and assist patients in overcoming their condition.